2008
DOI: 10.1002/jrs.1876
|View full text |Cite
|
Sign up to set email alerts
|

Excess thermodynamic properties in liquid binary mixtures

Abstract: Excess volumes and adiabatic compressibility have been measured in several binary liquid mixtures to answer the question whether structural information can be gained through the analysis of the concentration dependence of the excess quantities. The obtained results are compared with independent indications from Raman spectroscopy, which is able to probe directly the occurrence and the nature of effective intermolecular interactions. Some doubts have arisen against the usual approach adopted for estimating the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Aliotta et al [182] discuss theoretically excess thermodynamic properties in liquid binary mixtures based on experimental Raman and Brillouin data. A Raman and DFT study of hydrogen-bonded 2-and 3-chloropyridine with methanol is reported by Singh et al [183] The mole-fraction-dependent linewidth and vibrational mode peak position have been determined to derive vibrational dephasing times.…”
Section: Studies In Binary Mixturesmentioning
confidence: 99%
“…Aliotta et al [182] discuss theoretically excess thermodynamic properties in liquid binary mixtures based on experimental Raman and Brillouin data. A Raman and DFT study of hydrogen-bonded 2-and 3-chloropyridine with methanol is reported by Singh et al [183] The mole-fraction-dependent linewidth and vibrational mode peak position have been determined to derive vibrational dephasing times.…”
Section: Studies In Binary Mixturesmentioning
confidence: 99%
“…The thermodynamic and kinetic properties of these systems has led to a better comprehension of this extraordinary, vital liquid at a molecular level. 15 For instance, the knowledge of separate dynamics of solvent and solute molecules in aqueous solutions will be helpful in developing a general understanding about hydration in biology and solution chemistry. 16 Moreover, the structure and dynamics of liquid water with special concern to the hydrogen-bond (HB) network have been debated.…”
Section: The 2007 Meeting In Cataniamentioning
confidence: 99%